PEMBERDAYAAN MASYARAKAT DUSUN JATEN, MRICO DAN BRUNO 1 UNTUK MENINGKATKAN KETAHANAN PANGAN DENGAN PEMANFAATAN POTENSI LOKAL - Dyah Suryani; Dwi Kurniawan; Deli Surya Melizan; Gusnardi Putra (Universitas Ahmad Dahlan, Yogyakarta, 2019)
Food security is a challenge that gets priority for achieving national prosperity in this millennium. Ngestirejo Village, Tanjungsari Subdistrict, Gunungkidul Regency has a lot of natural resources such as agriculture, plantations, livestock, and tourism. However, the use of this region's potential by the community is not optimal. This is because the community does not have the skills, experience, knowledge, and motivation to explore the potential of the region. This situation has long been occurring but there has been no effort either personally, the community, or the government to change this pattern of behavior with the willingness to utilize regional potential optimally. The condition of this problem occurred in 3 hamlets, namely Jaten Hamlet, Mrico Hamlet and Bruno 1 Hamlet. So to overcome these problems, the program was implemented, namely community empowerment to improve food security by utilizing local potential. Methods of implementing this program include: community education, technology diffusion and practice. The impact of the results of this activity is 1). Increased community insight, especially PKK mothers about utilizing local potential; 2) Increased community creativity in processing cakes from local potential results; 3) Increased entrepreneurial spirit for the community.